Leprosy: conformation, and decadence of the founding fact of the territory of Agua de Dios, Colombia - Nieto Gonzalez, Carlos Eduardo; Buitrago Echeverri, María Teresa; Rodríguez Arenas, María Stella (Estoa. Journal of the Faculty of Architecture and Urbanism, 2022)
The work makes a comprehensive approach to the social construction of the territory of the former lazareto of Agua de Dios (today municipality of Colombia) based on the social and political relations that have been defining its current configuration. Methodologically, it corresponds to an ethnographic case study. The work shows specific moments of the territorialization process built from the interaction of medical, political and religious powers over a confined population The way these logics have developed historically allows us to sustain the hypothesis that the evolution of leprosy - as a founding fact of this territory - has gradually lost the power to regulate territorial relations, hindering its reterritorialization, but maintaining the stigma towards the population.